2010
DOI: 10.5713/ajas.2010.90619
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Bioavailability of Organic Selenium Sources in Finishing Pigs

Abstract: This experiment was conducted to evaluate the bioavailability of different organic selenium (Se) products in finishing pigs. A total of 48 growing pigs, average body weight 47.6 kg±0.05, were allotted to four different treatments in a randomized complete block (RCB) design in three replicates with four pigs per pen. Three different organic Se products, Se-enriched yeast (treatments A and B) and Se-proteinate (treatment C), were used in conjunction with a basal diet with no added Se as a control treatment. In g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 19 publications
5
24
0
1
Order By: Relevance
“…Jiang, Tang, Xue, Lin, and Xiong () found higher deposition values of Se in pork meat to the organic source using Se yeast, and the highest deposition value was obtained with additional level of 0.5 ppm. Jang et al () and Lisiak et al () also found a higher Se deposition in muscle using Se yeast.…”
Section: Discussionmentioning
confidence: 86%
“…Jiang, Tang, Xue, Lin, and Xiong () found higher deposition values of Se in pork meat to the organic source using Se yeast, and the highest deposition value was obtained with additional level of 0.5 ppm. Jang et al () and Lisiak et al () also found a higher Se deposition in muscle using Se yeast.…”
Section: Discussionmentioning
confidence: 86%
“…The kidney is one of the most important organs for excretion and utilization of Se. Se content in pig kidneys is generally higher than in the liver or the muscle (Daun & Åkesson, 2004;Jang et al, 2010). In the present study, supplementation with Se up to 0.5 mg kg −1 of feed resulted in a significant increase in Se in the serum, liver, and muscle of pigs in comparison to the control group (0.3 mg Se kg −1 feed).…”
Section: Effects Of Selenium and Vitamin E Supplementation 197mentioning
confidence: 50%
“…Sodium selenite seems to be more effective in enhancing the activity of serum glutathione peroxidase (GSHPx) than organic Se, particularly at lower dietary Se levels, but less is retained in the tissues . Jang et al (2010) reports that the period of Se supplementation should be determined based upon the chemical forms and organic sources of Se to maximize the retention of Se in tissues or produce Se-fortified animal products as a functional food. Organic Se is more recommended in dietary supplementation of pigs due to the fact that mineral Se, widely used in pigs' fodders, is not always sufficient.…”
Section: Effects Of Selenium and Vitamin E Supplementation 197mentioning
confidence: 99%
“…Conversely, no effect of organic Cr supplementation for swine was described by Matthews et al (2001Matthews et al ( , 2005. A similar situation occurred with organic Se for pigs: positive effects on performance and carcass characteristics were described in some trials (JANG et al, 2010;MARTINEZ-GOMEZ et al, 2012), but a lack of effect on these characteristics was described in others (STUPKA et al, 2012;CAMPOS, 2013).…”
Section: Introductionmentioning
confidence: 83%
“…Xu et al (2017) also showed better feed conversion in swine supplemented with Cr methionine with or without Zn sulfate from 50 to 110 kg of BW. Comparing the effects of 0.3 mg kg -1 of Se protein and Se-enriched yeast, Jang et al (2010) described better performance in pigs supplemented with the first additive, suggesting that Se protein has higher bioavailability to pigs than Se-enriched yeast. Differences in the bioavailability of organic Cr and Se between sources could be the reason for such discrepant results in the literature.…”
Section: Resultsmentioning
confidence: 99%